Readout Methods to Enhance the Performance of Luminescence Thermometers - Miroslav D. Dramićanin; Abdullah N. Alodhayb; Aleksandar Ćirić (Condensed Matter)
Over the past three decades, luminescence thermometry has gained significant attention among researchers and practitioners. The method has progressed in terms of utilizing temperature-sensitive luminescent materials, obtaining temperature read-outs from luminescence, developing applications, and improving performance. This paper reviews and critically analyzes routes for improving luminescence thermometry performance, in particular the sensitivity, accuracy, and precision of the method. These include the use of highly temperature-sensitive probes, temperature read-outs from luminescence with improved sensitivity, multiparameter temperature-reading methods, the applications of principal component analysis and artificial neural networks, and sensor fusion.